Mission and Sustainability of Informatics for Integrating Biology and the Bedside (i2b2) - Murphy, Shawn (EGEMS (Wash DC), 2014)
INTRODUCTION: A visible example of a successfully disseminated research project in the healthcare space is Informatics for Integrating Biology and the Bedside, or i2b2. The project serves to provide the software that can allow a researcher to do direct, self-serve queries against the electronic healthcare data form a hospital. The goals of these queries are to find cohorts of patients that fit specific profiles, while providing for patient privacy and discretion. Sustaining this resource and keeping its direction has always been a challenge, but ever more so as the ten year National Centers for Biomedical Computing (NCBCs) sunset their funding. FINDINGS: Building on the i2b2 structures has helped the dissemination plans for grants leveraging it because it is a disseminated national resource. While this has not directly increased the support of i2b2 internally, it has increased the ability of institutions to leverage the resource and generally leads to increased institutional support. DISCUSSION: The successful development, use, and dissemination i2b2 has been significant in clinical research and informatics. Its evolution has been from a local research data infrastructure to one disseminated more broadly than any other product of the National Centers for Biomedical Computing, and an infrastructure spawning larger investments than were originally used to create it. Throughout this, there were two main lessons about the benefits of dissemination: that people have great creativity in utilizing a resource in different ways and that broader system use can make the system more robust. One option for long-term sustainability of the central authority would be to translate the function to an industry partner. Another option currently being pursued is to create a foundation that would be a central authority for the project. CONCLUSION: Over the past 10 years, i2b2 has risen to be an important staple in the toolkit of health care researchers. There are now over 110 hospitals that use i2b2 for research. This open-source platform has a community of developers that are continuously enhancing the analytic capacities of the platform and inventing new functionality. By understanding how i2b2 has been sustained, we hope that other research infrastructure projects may better navigate options in making those initiatives sustainable over time.